Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) dengan Bantuan Praktikum Terhadap Hasil Belajar Fisika - Yola Allan Sembiring; Destiniar Zagoto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2017)
The research purpose to know the Influence of cooperative learning type Think Pair Share (TPS) with practical assistance to the learning outcomes of students in physics class X SMA ANGKASA 1 Jakarta Timur. Type of research is a quasi experimental design using pretest-posttest-control-group design. Sampling using cluster random sampling, acquired two classes, X MIA 1 into experimental class and class X MIA 2 as control class. The instrument comes in the form of multiple choice tests. From the research results obtained by the test value gain on an experimental class of 0.74 which is in the high category and control class is 0.43 which is in the low category. Based on t-test with SPSS version 16, the obtained results sig. (2-tailed) was 0.000 <0.05, so it can be expressed Ha is accepted and Ho is rejected. There can be concluded that the significant influence of cooperative learning model TPS to learning outcomes. Keywords: cooveratif, Think Pair Share, quasi eksperimental, learning outcome.